Regulation of actin-Spectrin cytoskeleton by ICA69 at the Drosophila neuromuscular junction. Issue 1 (2nd January 2018) - Mallik, Bhagaban; Kumar, Vimlesh
ABSTRACT: Bin-Amphiphysin-Rvs (BAR) domain containing proteins with their membrane deforming properties have emerged as key players in shaping up neuronal morphology and regulating cytoskeletal dynamics. However, the in vivo contexts in which BAR-domain proteins integrate membrane dynamics with cytoskeletal rearrangements remain poorly understood. Recently, we identified islet cell autoantigen 69 kDa as one of the N-BAR-domain containing proteins which regulate synaptic development and organization at the Drosophila neuromuscular junction. ICA69 genetically functions downstream of Rab2 to regulate synapse morphology. We found that ICA69 alters Spectrin level at the Drosophila NMJ, and redistributes actin regulatory proteins in cultured cells suggesting that ICA69 may regulate NMJ organization by regulating actin-Spectrin cytoskeleton. We propose a model in which ICA69 genetically interact with components of actin regulatory proteins for cytoskeleton dynamics to regulate NMJ development and synapse organization.